Effect of oregano essential oil against selective microorganisms in raw mutton - Islam, MS; Nila, JS; Fariha, S; Hassan, S (Meat Research, 2024)
The current study was conducted to ascertain the impact of various concentrations of oregano essential oil on the microbial population in raw mutton. The experiment was conducted using a complete randomized design (CRD) with six (6) treatments as T0 , T1 , T2 , T3 , T4 , T5 and three (3) replications. The drop plate method was utilized to detect the presence of certain microorganisms. The outcomes showed that adding oregano oil reduced the microbial population in samples. Colony-forming units gradually decreased where T5 being the lowest number of colony-forming units. There was a highly significant difference (p<0.0001) in the colony-forming unit of Staphylococcus epidermidis and Proteus vulgaris. For Klebsiella pneumonia, there was a significant reduction (p<0.01) of the microbes among samples. On the other hand, Staphylococcus epidermidis significantly outperformed Proteus vulgaris in terms of growth inhibition. In light of the findings, it is possible to conclude that the addition of oregano essential oil at a 200 µl level reduces the microbial population of raw mutton.